2018
DOI: 10.1029/2018sw001995
|View full text |Cite
|
Sign up to set email alerts
|

Space Weather Events, Hurricanes, and Earthquakes in Mexico in September 2017

Abstract: In the interval of 4–10 September 2017, the Sun presented multiple solar flares from active region AR 2673. There were also coronal mass ejections that interacted with the Earth's magnetosphere. This solar activity produced several space weather events. These events were observed with ground‐based instruments of the Mexican Space Weather Service. The Mexican Array RadioTelescope detected highly perturbed solar transits associated with Type I radio emissions from active regions. The Compact Astronomical Low‐fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…The contemporary importance of such advice is demonstrated by recent experience in Mexico in September 2017, when severe space weather coincided with the impact of a hurricane and a major earthquake. Scientific advice was important in helping civil protection authorities to address these different hazards and, most importantly, to counter scare‐mongering that created unnecessary public anxiety about the coincidence of these hazards (Gonzalez‐Esparza et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The contemporary importance of such advice is demonstrated by recent experience in Mexico in September 2017, when severe space weather coincided with the impact of a hurricane and a major earthquake. Scientific advice was important in helping civil protection authorities to address these different hazards and, most importantly, to counter scare‐mongering that created unnecessary public anxiety about the coincidence of these hazards (Gonzalez‐Esparza et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The September 2017 events included an X9.3 flare and a G4 magnetic storm (Redmon et al, ). In addition, Gonzalez‐Esparza et al () reported the September 2017 space weather events detected by the Mexican ground‐based instrumental network.…”
Section: Study Of Four Geomagnetic Stormsmentioning
confidence: 99%
“…In Latin America, specially in Argentina, Brazil, Mexico and Peru, interest in space weather studies has become more important in the last decade (Denardini et al, 2016a,b,c;Hysell et al, 2018;Valladares and Chau, 2012). Currently, in Brazil and Mexico, regional GNSS-based TEC maps are systematically generated in order to assimilate them into space weather forecasting models (Gonzalez-Esparza et al, 2017;Takahashi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%